Nizatidine treatment and its relationship with leptin levels in patients with olanzapine-induced weight gain - Atmaca, M; Kuloglu, M; Tezcan, E; Ustundag, B (Wiley, 2003)
It has been reported that nizatidine may reduce the weight gain in schizophrenic patients receiving olanzapine treatment. Previous studies have demonstrated a relation between olanzapine-induced weight gain and serum leptin levels. Therefore, in the present study, it was planned to investigate the efficacy of nizatidine on the treatment of olanzapine-induced weight gain, and if available, whether leptin levels were associated with reductions in weight gain. Of the patients with schizophrenia on olanzapine treatment, 59 who gave informed consent entered a 3 month open-label screening period. Of them, 35 patients (59%) showed weight gain in excess of 2.5 kg. These patients were randomly divided into two groups; olanzapine plus nizatidine (group 1) and olanzapine plus placebo (group H) for an 8-week double-blind phase. The patients were evaluated at the baseline and at week 8 with respect to the positive and negative syndrome scale, body mass index, weight and serum leptin levels. In the open-label period, olanzapine led to a considerable marked increase in weight and in serum leptin levels. There was no statistically significant difference between the groups with respect to weight at the beginning of the 8-week double-blind treatment period. Throughout the 8 week double-blind period, in group 1, the weight decreased by 4.5 +/- 2.2 kg (p < 0.05). In contrast, weight increased in group II by a mean of 2.3 +/- 0.9 kg (p > 0.05). The leptin levels decreased by 4.4 +/- 2.3 ng/ml in group I (p < 0.01), and increased by 1.8 +/- 0.6 ng/ml in group II (p > 0.05). These changes were accompanied by changes in the leptin levels in both groups I and II. It is concluded that leptin seems to be strongly associated with olanzapine-induced weight gain and that nizatidine treatment may reduce the weight gain and the correlated leptin levels in patients with schizophrenia on olanzapine treatment. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: leptin; nizatidine; olanzapine; weight gain